Pelatihan 4M (Melihat-Menyusun-Mengeja-Membaca) untuk Anak Slow Learner - Lusia Gayatri Yosef (Jurnal Psikologi, 2012)
A student grade 1 of elementary school (n=1) participated in this 4M training. The student was diagnosed as a slow learner child. Purpose of the 4M training is to increase student's reading ability. Before participating in the 4M training, the child should be prepared (joined) the alphabet training. After having ability to pronounce alphabet correctly, the student was allowed to participate at the 4M training. This 4M training used pictures in order to explain the words. This research revealed that there was a significant difference on student’s vocabulary mastery, before and after the 4M training (chi square =23, 468, df= 6, p< 01). After training, the number of the readable words was increasing.